The great migration - Harris, Duchess; Conley, Kate A., 1977- (Minneapolis, Minnesota : Core Library, 2020)
Between 1916 and 1970, more than 6 million African Americans migrated from the South to the North. They wanted to escape racial violence in the South. This mass movement of people is called the Great Migration. This book explores the history of the migration and its legacy.
Includes bibliographical references (page 46) and index.
6.2.
3-6.
770L
Keywords: African Americans -- Social conditions -- Juvenile literature; Black people -- Relocation -- Juvenile literature; Rural-urban migration; African Americans -- Social conditions